2015
DOI: 10.18632/oncotarget.4318
|View full text |Cite|
|
Sign up to set email alerts
|

Trop-2 is a novel target for solid cancer therapy with sacituzumab govitecan (IMMU-132), an antibody-drug conjugate (ADC)*

Abstract: Trop-2 is a novel target for ADC therapy because of its high expression by many solid cancers. The rational development of IMMU-132 represents a paradigm shift as an ADC that binds a well-known moderately-cytotoxic drug, SN-38, to the anti-Trop-2 antibody. In vitro and in vivo studies show enhanced efficacy, while there is a gradual release of SN-38 that contributes to the overall effect. IMMU-132 is most efficacious at a high drug:antibody ratio (DAR) of 7.6:1, which does not affect binding and pharmacokineti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
288
1
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 357 publications
(301 citation statements)
references
References 49 publications
(84 reference statements)
10
288
1
2
Order By: Relevance
“…IMMU-132 was found to deliver much higher levels of SN-38 to tumors than irinotecan and, importantly, all of the SN-38 delivered to the tumor by IMMU-132 is released in its most potent form. In relationship to gastrointestinal toxicity, the much lower amounts of SN-38G in the serum and significantly lower amounts of SN-38/SN38G in the intestine with IMMU-132 are expected to reduce the risk for severe diarrhea in patients, which is confirmed in clinical studies (34)(35)(36)(37)(38). Thus, IMMU-132 is an ADC that appears to have unique properties that combine to make an effective therapeutic agent in the solid cancers tested.…”
Section: Discussionmentioning
confidence: 84%
“…IMMU-132 was found to deliver much higher levels of SN-38 to tumors than irinotecan and, importantly, all of the SN-38 delivered to the tumor by IMMU-132 is released in its most potent form. In relationship to gastrointestinal toxicity, the much lower amounts of SN-38G in the serum and significantly lower amounts of SN-38/SN38G in the intestine with IMMU-132 are expected to reduce the risk for severe diarrhea in patients, which is confirmed in clinical studies (34)(35)(36)(37)(38). Thus, IMMU-132 is an ADC that appears to have unique properties that combine to make an effective therapeutic agent in the solid cancers tested.…”
Section: Discussionmentioning
confidence: 84%
“…Even so, 5-year survival rate is only 16%, though new drugs of anti-lung cancer such as angiogenesis-targeted drugs, epidermal growth factor receptor (EGFR)-targeted drugs, protein peptides of anti-lung cancer and lung cancer antibody drugs were developed. [97][98][99][100][101][102] Recently, a study reported that nanoliposomes using sodium hyaluronate and trimethyl CS form polymer-glycerosomes that can effectively deliver CUR to lung so as to improve the therapeutic index of CUR. 103 Recently, many studies reported that CUR liposomes have anticancer activity.…”
Section: Lung Cancermentioning
confidence: 99%
“…The association of Trop-2 expression with advanced disease and/or clinical outcome in multiple tumor types, and the relatively restricted expression in normal adult tissues, underscores the potential benefit of targeting Trop-2 to fill an unmet need in cancer treatment. An anti-Trop-2 SN38 conjugate, hRS7-CL2A-SN-38 (IMMU-132), consisting of a humanized Trop-2 antibody conjugated to SN38, the active component of irinotecan, has been shown to be efficacious in several epithelial cancer cell line xenograft models (20)(21)(22). IMMU-132 (sacituzumab govitecan) is currently being tested in clinical trials for solid tumors and has reported encouraging therapeutic activity in patients with difficult-to-treat cancers (23).…”
Section: Introductionmentioning
confidence: 99%